Association between inflammatory bowel disease and risk of stroke: a systematic review and meta-analysis of cohort studies - Fan, Jin-Shan; Wang, Meng; Chen, Ni; Sun, Bai-chao; Zhang, Qi-Bing; Li, Yong; Huang, Ming-Jie (Frontiers in Neurology, 2023)
Background/objectives Recently, four meta-analyses have explored the association between inflammatory bowel disease (IBD) and the risk of stroke. These studies have demonstrated that people with IBD may be at an increased risk of stroke. However, some limitations such as high heterogeneity and the lack of uniformity in the types of research, especially the reuse of some sample sizes, cannot be neglected. These factors reduce the credibility of their research conclusions. Therefore, we conducted a meta-analysis to explore this possible association. Methods PubMed, Embase, and Web of Science were searched from inception to 30 June 2023. A random effects model with the generic inverse variance method was used in this meta-analysis. The Review Manager software was used to obtain all relative risks (RRs) and their 95% confidence intervals (CIs). Publication bias was tested, and sensitivity and subgroup analyses were conducted to explore possible heterogeneities. Results This meta-analysis included 12 cohort studies (involving 4,495,055 individuals). Meta-analysis of these data has shown that IBD was associated with an increased risk of stroke (RR = 1.19, 95%CI:1.14-1.24, p < 0.00001). Our results were stable and robust in subgroup and sensitivity analyses. Conclusions Our results suggest that IBD is associated with an increased risk of stroke. To reduce the incidence of stroke, patients with IBD are encouraged to undergo stroke risk assessments, especially for young female patients; assessing the risk of ischemic stroke is of particular importance. Prospective studies considering stroke subtypes, IBD severity and treatments, regions, and other confounding factors are needed to further explore the nature of each association. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022373656.